Comparison of Fracture Resistance of the Endodontically Treated Roots with Two Sealer Types: An In Vitro Study - Neda Hajihassani; Soolmaz Heidari; Mohammad Ghanati; Navid Mohammadi (Wolters Kluwer Medknow Publications, 2022)
Introduction: This study aimed to compare the fracture resistance using a bioceramic sealer and an epoxy resin-based sealer. Materials and Methods: One hundred maxillary central incisors were randomly assigned to three experimental groups: AH Plus sealer using the single-cone technique, AH Plus sealer using the lateral compaction technique, SureSeal Root sealer, and two positive and negative control groups. Then the fracture resistance of the prepared tooth roots was determined. The data were analyzed with one-way ANOVA and Tukey Post Hoc tests. Results: There were statistically significant differences between the five study groups (P < 0.001). There was no significant difference between the negative control and Sureseal groups (P = 0.183). There were significant differences between the SureSeal and AH Plus groups (P < 0.05). Conclusion: SureSeal Root sealer significantly increased the fracture resistance of the teeth compared to AH Plus sealer.